High levels of serum soluble TWEAK are associated with neuroinflammation during multiple sclerosis - Adil Maarouf; Delphine Stephan; Marie-Pierre Ranjeva; Jean-Philippe Ranjeva; Jean Pelletier; Bertrand Audoin; Michel Khrestchatisky; Sophie Desplat-Jégo (Journal of Translational Medicine, 2019)
Abstract Background Inflammation and demyelination are the main processes in multiple sclerosis. Nevertheless, to date, blood biomarkers of inflammation are lacking. TWEAK, a transmembrane protein that belongs to the TNF ligand family, has been previously identified as a potential candidate. Methods Twenty-eight patients (9 males, 19 females) were prospectively included after a first clinical episode suggestive of multiple sclerosis and clinically followed during 3 years. Fifty-seven healthy controls were also included. TWEAK serum levels and MRI exams including magnetization transfer imaging were performed at baseline, 6- and 12-month follow-up. Results TWEAK serum levels were significantly increased in the patient group (mean baseline = 1086 ± 493 pg/mL, mean M6 = 624 ± 302 pg/mL and mean M12 = 578 ± 245 pg/mL) compared to healthy controls (mean = 467 ± 177 pg/mL; respectively p < 0.0001, 0.01 and 0.06). Serum levels of soluble TWEAK were significantly increased during relapses, compared to time periods without any relapse (respectively 935 ± 489 pg/mL and 611 ± 292 pg/mL, p = 0.0005). Moreover, patients presenting at least one gadolinium-enhanced CNS lesion at baseline (n = 7) displayed significantly increased serum TWEAK levels in comparison with patients without any gadolinium-enhanced lesion at baseline (n = 21) (respectively 1421 ± 657 pg/mL vs 975 ± 382 pg/mL; p = 0.02). Finally, no correlation was evidenced between TWEAK serum levels and the extent of brain tissue damage assessed by magnetization transfer ratio. Conclusions The present study showed that TWEAK serum levels are increased in MS patients, in relation to the disease activity. This simple and reproducible serum test could be used as a marker of ongoing inflammation, contributing in the follow-up and the care of MS patients. Thus, TWEAK is a promising serum marker of the best window to perform brain MRI, optimizing the disease control in patients.